2017
DOI: 10.1186/s40360-017-0135-8
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside contributes to reducing blood pressure and alleviating cerebrovascular contractile activity in diabetic Goto-Kakizaki Rats by inhibition of L-type calcium channel in smooth muscle cells

Abstract: BackgroundVascular disease is a common and often severe complication in diabetes mellitus. Hyperglycemia and hypertension are considered to be two of the leading risk factors for vascular complications in diabetic patients. However, few pharmacologic agents could provide a combinational therapy for controlling hyperglycemia and blood pressure in diabetic patients at the same time. Salidroside (SAL) is the major active ingredient derived from Rhodiola. Recently, it has been reported that SAL have an obvious hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Salidroside is the main bioactive component in Rhodiola rosea and possesses several biological and pharmacological properties, such as anti-inflammatory, anti-oxidative, anti-aging, anti-cancer, anti-depressant, neuroprotective, and hepatoprotective activities [13,14]. In addition, salidroside has been shown to reduce blood pressure and alleviate cerebrovascular contractile activity in diabetic Rats [15], and attenuate oxidized low-density lipoprotein-induced endothelial cell injury [16] or vascular endothelial dysfunction [17]. Furthermore, salidroside has also been demonstrated to decrease atherosclerotic plaque formation in mice with deficiency of low-density lipoprotein receptor [18] and ameliorate chronic hypoxia-induced pulmonary arterial hypertension in mice [19].…”
Section: Agingmentioning
confidence: 99%
“…Salidroside is the main bioactive component in Rhodiola rosea and possesses several biological and pharmacological properties, such as anti-inflammatory, anti-oxidative, anti-aging, anti-cancer, anti-depressant, neuroprotective, and hepatoprotective activities [13,14]. In addition, salidroside has been shown to reduce blood pressure and alleviate cerebrovascular contractile activity in diabetic Rats [15], and attenuate oxidized low-density lipoprotein-induced endothelial cell injury [16] or vascular endothelial dysfunction [17]. Furthermore, salidroside has also been demonstrated to decrease atherosclerotic plaque formation in mice with deficiency of low-density lipoprotein receptor [18] and ameliorate chronic hypoxia-induced pulmonary arterial hypertension in mice [19].…”
Section: Agingmentioning
confidence: 99%
“…The content of salidroside in the crude FLL power determined by HPLC ranges from 5.7 to 6.9 mg/g [ 42 ]. Currently, there are more than 400 publications investigating the biological activities of salidroside, including anti-diabetes [ 43 ], anti-obesity [ 44 ], anti-cancer [ 44 , 45 ], anti-osteoporosis [ 46 ], anti-arthritis-induced brain cognition deficits [ 47 ], anti-hypertension [ 48 , 49 ], and cardioprotective effects [ 50 ].…”
Section: Phytochemistry Of Fructus Ligustri Lucidimentioning
confidence: 99%
“…Autophagy confers protective effect against toxicity of anti-tumor agents, thus it, to some extent, inhibits apoptosis of cancerous cells and results in chemo-resistance [ 17 ]. Sal has been emerged as an important plant extracts for the treatments of cancer and age-related diseases [ 18 ]. Our data showed that Sal inhibited cell viability of CRC, but only exerted modest effect on the apoptosis at a moderate concentration (1 μg/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has demonstrated that Sal exerts anti-proliferative and pro-apoptotic effects against cancer cells [ 18 ]. However, the present study found that Sal also triggered autophagy of CRC cells, which counteracts the anti-tumor effects of Sal alone or in combination with anti-tumor agents (as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%